Analisis Penerapan ISO 45001:2018 Terhadap Risiko Keselamatan dan Kesehatan Kerja Pada Karyawan di PT Moya Tangerang Tahun 2023 - Nur’aini, Siti Khofifah; Agustina, Agustina; Veronica, Rina (STIKes Persada Husada Indonesia, 2024)
According to Government Regulation Number 50 of 2012 concerning the implementation of SMK3 as an effort to prevent work accidents and work-related diseases. ISO 45001:2018 is an international standard regarding SMK3. Based on BPJS data, the number of work accidents always increases every year. The increase in the number of work accident cases has become a problem so it is necessary to research to see the application of SMK3 in PT Moya Tangerang. This study aims to describe the implementation of ISO 45001:2018 on OHS risks for employees at PT Moya Tangerang in 2023, identifying K3 risks, analyzing K3 risk assessments, and knowing K3 risk control efforts. The research uses qualitative research with in-depth interviews, observations, and document reviews. The results of this research have achieved 90% implementation of ISO 45001:2018, but the company already has ISO 45001:2018 certification. In the hazard identification process, 5 areas are identified as having a risk of work accidents, namely the areas of operation, maintenance, laboratory, general affairs, and logistics. The risk assessment process found 12 risks at a low level, 50 risks at a moderate level, 53 at a high level, and 44 risks at the extreme level. The risk control process is carried out using substitution, technical, administrative, and PPE controls. The suggestion in this research is that companies need to maintain their commitment to occupational safety and health (K3) and fulfill other normative references in implementing the occupational safety and health management system.